ANALYSIS OF THE INFLUENCE OF OPEN UNEMPLOYMENT, HUMAN CAPITAL AND POPULATION ON POVERTY IN NORTH SUMATRA - Erza, Datuk Sazli Daffa Yudha; Marito, Cinta; Nisa, Fadila; Pardede, Nova; Sinaga, Defrin; Hidayat, Nasrullah (Universitas Negeri Medan, 2023)
This research aims to find out how much influence the unemployment rate, human capital and population have on poverty in the 2018-2022 period. This research uses quantitative methods with descriptive analysis. The data used in this research is secondary data sourced from the North Sumatra Central Statistics Agency (BPS) for 5 years from 2018-2022. The data analysis technique uses the Fixed Effect Model based on the results of the Chow test and Hausman test. The research results show that (1) the independent variables, namely open unemployment, human capital, and population have a significant effect on poverty in North Sumatra province, (2) the level of open unemployment has a positive and significant effect on poverty in North Sumatra, (3) the Human variable Capital has a negative and significant effect on poverty in North Sumatra, and (4) the population variable has a positive and insignificant effect on poverty in North Sumatra